ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS SIKLUS PENGGAJIAN KARYAWAN (Studi Kasus Pada PT PLN (Persero) Distribusi Jawa Timur Area Malang) - Dyah Ratna Kusumawardhani; Wiwik Hidajah Ekowati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objective of research is to analyze the internal control system of employee payroll cycle which is applied at PT PLN (Persero) of East Java Distribution for Malang Area. Employee payroll cycle begins by recording attendance timing using Fingerprint Machine and ends with the bank transferring money the payroll to the account of each employee. Research type is descriptive study which is to develop a concept and to compile the facts but without testing the hypothesis. It is aimed at giving description about situation and condition which can be obtained through interview, observation and documentation. Result of research is evaluated and given suggestion for the improvement. Result of analysis concludes that the implementation of accounting information system and internal control of employee payroll cycle which is applied at PT PLN (Persero) of East Java Distribution for Malang Area is already good, meaning that it complies with the standard and procedure stated by company. The system has been computer-based, which is called System Application and Product in Data Processing (SAP). Some improvements are needed to deal with weaknesses. These weaknesses are the lack of limitation on the use of Internet technology, the data storage shelf that is highly subjected to theft and damage, and some employees who not optimally using their work hour.Keywords: Payroll, Payroll Information System, Internal Control, Payroll Internal Control, and Computerization.